(untitled) (Research, Society and Development, 2022)
Objective: To report the outcomes observed in the treatment of patients with Bipolar Affective Disorder during pregnancy. Methodology: This is descriptive research of the integrative review type. Studies published between 2000 and 2022 were considered, obtained from scientific databases that cover relevant sources inherent to the topic, using as one of the main criteria the selection of original and current articles. In all, 27 articles that addressed the topic were analyzed. Results: The use of lithium should be done with reservations, due to the risk of neural defects in the fetus, in addition to the close monitoring of the pregnant woman’s lithemia. Anticonvulsants also have a risk of neural defects, in addition to the possibility of alteration in the metabolism of contraceptives, with the risk of unwanted pregnancy. Atypical antipsychotics pose no risk to the fetus, except for risperidone. Those with a higher metabolic profile, such as quetiapine and olanzapine, have a higher risk of developing gestational diabetes. Conclusion: The mood control of patients with bipolar disorder must be competently monitored by the health professional, who must be equipped with all therapeutic options, so that he can present them to patients, thus obtaining a shared strategy with greater chances of success.